Primary aldosteronism is associated with risk of urinary bladder stones in a nationwide cohort study - Mu-Chi Chung (Nature Portfolio, 2021)
Abstract We analyzed database from the Taiwan National Health Insurance to investigate whether primary aldosteronism (PA) increases the risk of bladder stones. This retrospective nationwide population-based cohort study during the period of 1998–2011 compared patients with and without PA extracted by propensity score matching. Cox proportional hazard models and competing death risk model were used to estimate the hazard ratios (HRs), sub-hazard ratios (SHRs) and corresponding 95% confidence intervals (CIs). There were 3442 patients with PA and 3442 patients without PA. The incidence rate of bladder stones was 5.36 and 3.76 per 1000 person-years for both groups, respectively. In adjusted Cox hazard proportional regression models, the HR of bladder stones was 1.68 (95% CI 1.20–2.34) for patients with PA compared to individuals without PA. Considering the competing risk of death, the SHR of bladder stones still indicates a higher risk for PA than a comparison cohort (SHR, 1.79; 95% CI 1.30–2.44). PA, age, sex, and fracture number were the variables significantly contributing to the formation of bladder stones. In conclusion, PA is significantly associated with risk of bladder stones.